2012
DOI: 10.2807/ese.17.04.20066-en
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive antibody to swine influenza A(H3N2) subtype virus in children and adults before and after immunisation with 2010/11 trivalent inactivated influenza vaccine in Canada, August to November 2010

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
6
19
0
2
Order By: Relevance
“…These data are consistent with human serologic studies demonstrating that immunization with the 2010-2011 TIV has no impact on the level of cross-reactive A(H3N2)v antibodies in immunologically naive children (age, Ͻ3 years) and failed to substantially improve the level of cross-reactive antibodies in adults (17,18). Because the majority of the population lacks specific immunity against this new virus variant, an A(H3N2)v-specific vaccine is needed for optimal protection for all ages.…”
supporting
confidence: 79%
“…These data are consistent with human serologic studies demonstrating that immunization with the 2010-2011 TIV has no impact on the level of cross-reactive A(H3N2)v antibodies in immunologically naive children (age, Ͻ3 years) and failed to substantially improve the level of cross-reactive antibodies in adults (17,18). Because the majority of the population lacks specific immunity against this new virus variant, an A(H3N2)v-specific vaccine is needed for optimal protection for all ages.…”
supporting
confidence: 79%
“…Along with the unique genotype and HA cluster, the N2 gene is derived from a human seasonal virus from 2002 instead of the N2‐1998 lineage associated with the original swine H3N2‐TRIG virus . Data show that current trivalent human influenza vaccine generates minimal HI cross‐reactivity and would likely provide no protection for this virus . Similar data evaluating swine vaccines or population immunity in swine herds against contemporary H3N2 have not been reported previously.…”
Section: Introductionsupporting
confidence: 58%
“…Given their importance in viral replication and virulence, it is probable that these segments played significant roles in the observed RD transmission. More importantly, our serologic results and of others clearly showed that our reassortant H3 isolates are antigenically divergent from recent human seasonal H3N2 strains. Therefore, previous exposure to or immunization with trivalent influenza vaccines may not elicit protective immunity against infection from these novel H3 viruses.…”
Section: Discussionsupporting
confidence: 71%